Implementation of Raw Material Inventory Control System to Increase Sales of Hand Batik: Implementasi Sistem Pengendalian Persediaan Bahan Baku Untuk Meningkatkan Penjualan Batik Tulis - Fajri, Rihan; Nurasik, Nurasik (Indonesian Journal of Innovation Studies, 2023)
This study aims to explain about how to control the supply of raw materials in the Batik Tulis Trading Business "Jetis Sidoarjo". The method used in the quantitative approach. The research approach in this thesis uses a quantitative research approach with a descriptive approach. In the object of this research, namely the implementation of a raw material inventory control system to improve the quality of batik production in Kampoeng Batik Tulis Jetis SMEs. The subjects in this research are the UMKM Kampoeng Batik Tulis Jetis, Lemahpuro Village, Sidoarjo District, Sidoarjo Regency, East Java. With descriptive research, the researcher only intends to describe (describe) or explain the symptoms that are currently happening. The results of this study can be concluded that using the calculation of safety stock and reordering is more effectively used in controlling raw material inventory when compared to current company policies. Companies can predict or avoid shortages or excess raw materials that can result in disruption of the production process by setting a safety stock calculation and also setting a re-order point, so the company can know or predict when to reorder and obtained with minimal inventory costs.